Exploring organizational consciousness: A critical approach towards organizational behavior - Muhammad Ajmal; Suleman Aziz Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Maintaining a higher level of organizational performance would always remain an active research focus. Increased complexity in business environment requires organizations to continuously revisit their human resources for augmented output. Organizational consciousness is a relatively new paradigm for analyzing organizational behavior that views organizations as self-consciousness entities. The analytical approach provided by organizational consciousness benefits OD practitioners and researchers to transform or bring about permanent changes in organizations. The purpose of the present article is to critically evaluate the literature available on organizational consciousness and set forth avenues for research in the domain. The article develops a conceptual foundation for researchers to explore new themes in the area.
Keywords: 330; corporate consciousness; global consciousness; organizational culture; organizational development (OD)